2015
DOI: 10.1055/s-0035-1545841
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Xanthones and Benzophenone from Garcinia smeathmannii

Abstract: A new prenylated xanthone, 1,3,5,8-tetrahydroxy-2-(3-methybut-2-enyl)-4-(3,7-dimethylocta-2,6-dienyl) xanthone (1), and a new benzophenone (2), together with four known xanthone derivatives, cheffouxanthone (3), smeathxanthone A (4), smeathxanthone B (5), ananixanthone (6), and two pentacyclic triterpenes, epi-friedelinol (7) and friedelin (8), were isolated from the stem bark of Garcinia smeathmannii. The structures of the compounds were elucidated on the basis of 1D and 2D NMR experiments, and compound 2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. Although xanthones have been reported to have good antibacterial activity, 32 the two new isolated xanthones (1 and 2) did not display any inhibitory activity against the tested bacteria.…”
Section: However Their Glycosylated Derivatives (3 and 4) Did Not DImentioning
confidence: 84%
“…Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. Although xanthones have been reported to have good antibacterial activity, 32 the two new isolated xanthones (1 and 2) did not display any inhibitory activity against the tested bacteria.…”
Section: However Their Glycosylated Derivatives (3 and 4) Did Not DImentioning
confidence: 84%
“…The 13 C NMR spectrum (Figure S3) displayed 14 resonances, which were classified by DEPT (distortionless enhancement by polarization transfer, Figure S3) experiments as one methyl, five aromatic methines, and eight non-protonated (including one ketone and seven aromatic) carbons (Table 1). The 1 H and 13 C NMR spectroscopic data (Figures S2–S6) are evocative of a benzophenone scaffold [13]. In the HMBC spectrum (Figure S6), the correlations from the proton of 2′-OH (Δ H 11.42) to C-1′, C-2′, and C-3′ located the OH group at C-2′, while the correlations from H-7′ (Δ H 2.18) to C-2′, C-3′, and C-4′ placed the methyl group at C-3′, and at last, the correlations from the OH proton at Δ H 9.02 to C-4′, C-5′, and C-6′ determined this OH group at C-5′.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] The xanthone compounds are also known to have many biological activities, such as antioxidants, antimicrobials, anti-inflammatory, anti-cancer and antihyperlipid. [34][35][36][37] In this review, there are 46 types of xanthone compounds which have been reported to have been isolated from the plant and more than half of them are prenylated xanthones. This is in accordance with a previous study which stated that the primary type of xanthone compounds in the Guttiferae family (G. dulcis) is prenylated xanthones.…”
Section: D) Xanthonementioning
confidence: 99%